Beyond the dichotomy between body and soul: notes on the “affinity argument” (77e-80d) in Plato’s Phaedo - Milione, Vitor de Simoni (Revista Archai, 2024)
The third argument in favor of the immortality of the soul in the Phaedo, which the exegetical tradition also calls the “affinity argument” (77e-80d), presents a curious relationship between body and soul, which is often seen by commentators as a radical dichotomy. To discuss this passage of the Phaedo in the attempt to surpass this alleged dichotomy sometimes imputed to Plato in this dialogue, we propose, in this article, a close analysis of the argument in two steps: (i) the analogy between the soul and the Forms (78b-79c), (ii) and the analogy between the soul and the divine (80a-c). Because this argument has been generating controversy and trusting that this debate is far from reaching its term, the objective of this article is to answer three questions: how are we to understand the affinity argument in the economy of the Phaedo? How are we to understand the relationship between body and soul in this argument? Finally, does the platonic text allows us to infer a radical dichotomy between these two elements?